2016
DOI: 10.1016/j.carres.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and solutions for chemical synthesis of syndecan-3 (53–62) glycopeptides with two heparan sulfate chains

Abstract: Proteoglycans play critical roles in many biological events. Due to their structural complexities, strategies towards synthesis of this class of glycopeptides bearing well-defined glycan chains are urgently needed. In this work, we give the full account of the synthesis of syndecan-3 glycopeptide (53–62) containing two different heparan sulfate chains. For assembly of glycans, a convergent 3+2+3 approach was developed producing two different octasaccharide amino acid cassettes, which were utilized towards synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 117 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…In turn, 3 can be generated using a cassette approach from glycosyl serine-glycine 4 building block followed by peptide chain elongation (Scheme 1). While previous synthesis utilized glycosyl serine as the cassette for peptide synthesis, 26,48 we found that the glycosylated serine was prone to base promoted glycan elimination (Fig. 2c) during coupling with peptides more than ve amino acids long.…”
Section: Synthetic Design Of Syndecan-4 Glycopeptidesmentioning
confidence: 80%
See 1 more Smart Citation
“…In turn, 3 can be generated using a cassette approach from glycosyl serine-glycine 4 building block followed by peptide chain elongation (Scheme 1). While previous synthesis utilized glycosyl serine as the cassette for peptide synthesis, 26,48 we found that the glycosylated serine was prone to base promoted glycan elimination (Fig. 2c) during coupling with peptides more than ve amino acids long.…”
Section: Synthetic Design Of Syndecan-4 Glycopeptidesmentioning
confidence: 80%
“…While many innovative methods to produce HS and heparin oligosaccharides have been established, [6][7][8][9][10][11][12] strategies for HS glycopeptide synthesis are underdeveloped. [24][25][26] Currently, structural features common in naturally existing HSPGs, such as aspartic acids in the core peptide and glycan chains bearing both O-and Nsulfates, are not accessible with the existing synthetic methods.…”
mentioning
confidence: 99%
“…Formation of glycosidic bonds to construct the oligosaccharides was challenging as several electron‐withdrawing groups reduce the nucleophilicity of glycosyl acceptors [40, 41] . Since electron‐withdrawing carboxy groups at C‐6 may further reduce the reactivity of the glucose donors, [42] they were introduced after the glycosylation. Finally, the densely nitrogen‐functionalized target molecules necessitated additional deprotection steps.…”
Section: Resultsmentioning
confidence: 99%
“…5b A levulinate ester (Lev), chloroacetate ester (ClAc), and a tert- butyldimethylsilyl ether (TBDMS) were chosen for testing due to their ability to potentially be removed in the presence of benzoyl esters and benzyl ethers (Table 2). In each case, compatibility between the glycosylation and the deprotection steps 5b,15 was observed in the automation cycles, giving 11 as a major product after FSPE purification as seen by HPLC analysis. Purification by HPLC allowed us to obtain the disaccharide 11 in 26% to 72% unoptimized yield depending on the protecting group and the glycosylation conditions used (Table 2).…”
mentioning
confidence: 89%